(untitled) (Advancements in Homeopathic Research, 2022)
The main cause of tooth loss in patients worldwide is inflammation of the pulp and the periapical tissues. Therefore, endodontics is one of the most rapidly developing specialities in dentistry. Despite proper endodontic treatment, in many cases it is not possible to determine the aetiology of the infection or the reason for its relapse. Many research studies indicate that infections of the periapical tissues are mainly caused by anaerobic bacteria. At present, frequently the composition of the micro flora within the inflammatory lesions is being evaluated with the use of molecular techniques, which showed that classical culture methods are not able to determine the aetiology of infections of the periapical tissues. The results of these studies contributed to the major changes in our understanding of the micro biome composition in the endodontium. Purulent endodontic lesions are particularly important, as they may lead to many severe – even life threatening – systemic complications.